Vitamin B complex deficiency after Roux-en-Y Gastric Bypass and Sleeve Gastrectomy - A systematic review and meta-analysis - Rita Correia da Silva Guerra Nunes (2021)
Background: Bariatric Surgery has been continuously chosen as a treatment for people with obesity and it has been proven to be beneficial in the improvement of comorbidities and quality of life. Albeit a very effective method, complications, such as nutritional deficiencies, are a possibility and should be taken into account. Aim: The aim of this systematic review and meta-analysis was to compare complex B vitamin deficiencies in patients with obesity submitted to Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG). Methods: A search was conducted using PUBMED, SCOPUS and the Cochrane Central Register of Controlled Trials. Reference lists from relevant articles were also searched. A random effects model was used to determine pooled estimates of the results. Results: Twenty-five Studies, comparing SG and RYGB and the effects of these surgeries on the deficiency of any of the B-complex vitamins were included in our systematic review. Of these, 21 studies were eligible for the meta-analysis, in which 5729 patients were included. Data was grouped into 3 time-frames relative to the time of surgery: short-term (<1 year), mid-term (>/= 1 year and <3 years) and long-term (>/= 3years). Our meta-analysis revealed a higher prevalence of vitamin B12 deficiency after RYGB in the short-term (OR= 1.47, 95%CI (1.04, 2.08); P= 0.03) and long-term period (OR=2.22, 95% CI (1.22, 4.04); P= 0.009) as well as in the pooled analysis (OR=1.66, 95% CI (1.29, 2.15); P= 0.0001). Mean serum values of B12 were significantly higher after SG in the long-term (MD= -50.17, 95% CI (-71.27, -29.08); P< 0.00001) and in the pooled analysis (MD= -44.78, 95%CI (-67.54, -22.02); P= 0.0001). Folate mean serum levels were significantly higher after RYGB in the mid-term (MD= 3.04, 95%CI (0.95, 5.12); P= 0.004) and in the pooled analysis (MD=2.56, 95% CI (0.89, 4.24); P= 0.003). Despite there being higher proportion of Vitamin B1 deficiency after SG in every timeframe, none of the results were statistically significant. Regarding vitamin B6, there was a higher proportion of patients with deficiency after SG in the pooled analysis (OR= 0.60, 95%CI (0.37, 0.95); P= 0.03). There was insufficient data to draw conclusions on B2 and B3 vitamins. Conclusion: In this systematic review and meta-analysis we concluded that SG was a better surgical method when concerning vitamin B12, as it caused less deficiency. On the other hand, Vitamin B6 deficiencies were less prevalent after RYGB and Folate mean levels were higher after RYGB. Further investigation regarding the impact of bariatric surgery on B-complex vitamins would be beneficial in order to confirm these results.